INTERFERENSI BAHASA KAILI KE DALAM BAHASA INDONESIA DI KOMISI PEMILIHAN UMUM (KPU) KABUPATEN SIGI - Hidayat, Hidayat; Nur, Yunidar; Harisah, Sitti (BAHASANTODEA, 2017)
Research are what is the form of interference Kailinese into Indonesian at General Election Commissions, Sigi regency? And what are the causes of interference Kailinese into Indonesian?. The type of research is qualitative by using descriptive method, recording technique, field notes, observation and interview. Data analysis technique used interactive analysis. The interference of Kailinesse into Indonesian in General Election Commissions involved form and factor causing interference. Researcher found the distribution of interfeence in the field of phonology, morphology, and syntax. Interference phonological forms found additional vocal phoneme /a/i/u/e/o/ at the end of the word, it called the language vocalist and busting phoneme /h/ at the beginning of the word and at the end of the word also have disappearance phoneme /k/p/t/n/ and replacement of the vocal phoneme /e/ to phoneme /a/ and phoneme /i/ to phoneme /e/ in the middle of the word. Inteference morphology include the prefix {mo-} compatible with prefix {ber-} in Indonesia, suffix {i-} compatible woth suffix {kan-} in Indonesian, whereas interference syntactic has found the use of clauses in sentences that deviate from the structure of Indonesian rule. Moreover, factors that affect the occurrence of interference, namely; (1) background speakers, (2) lack of vocabulary, (3) less skillful use of language, (4) the prestige of the source language, and (5) because of habits in the mother tongue.